Portayals of People with Disabilities in Indonesian Newsprint Media (A Case Study on Three Indonesian Major Newspapers) - Tsaputra Antoni (The Center for Disability Studies and Services Brawijaya University, 2016)
This article examines portrayals of people with disabilities in three Indonesian major newspapers (the web versions). The portrayals of people with disabilities in these newspapers are examined in terms of positive, negative or neutral tones (Clogston 1989, 1992). To determine the tones, the analysis is focussed on the qualitative content analysis of the articles. Overall, this article argues that portrayals of people with disabilities in Indonesian news print media may lead to positive or stereotypical view of society in looking at people with disabilities. The analysis of eleven stories from the Indonesian newspapers indicates that news on people with disabilities has yet to receive a priority for coverage. News on people with disabilities usually just appear in coincidence with the International Day of People with Disabilities on 3 December which is also in small number. Most of the stories analysed contain negative language which focuses on the impairments rather than the people. In fact, such negative portrayal can be avoided when the journalists have proper training and unprejudiced approach to disability issues.